Advancing the development of national childhood cancer care strategies in Latin America. (June 2017) - Denburg, Avram; Wilson, Michael G.; Johnson, Sonal i; Kutluk, Tezer; Torode, Julie; Gupta, Sumit
Highlights: Evidence-informed childhood cancer systems demand policy-oriented research. Optimal childhood cancer policy requires deliberative input from expert stakeholders. A pan-regional task force on childhood cancer would advance collective goals. Structured health system guidance is essential to national childhood cancer planning. There is a need for enhanced capacity for cancer system monitoring and evaluation. Abstract: Background: Despite a rising burden of cancer among children in low- and middle-income countries (LMICs), few efforts to develop system-wide strategies to combat childhood cancer exist. Such efforts are hampered both by gaps in research evidence and by weak links among stakeholders spanning the trajectory from research and care to policy. Deliberative dialogues have emerged as a promising means of advancing evidence-informed policy, by providing a structured forum for key stakeholders to integrate and explore scientific and experiential knowledge about complex health system issues. Methods: We convened a two-day deliberative forum with a broad array of stakeholders to collectively identify core problems, objectives, potential solutions, and key implementation considerations related to the development of national childhood cancer strategies in Latin America. Results: from this deliberative process describe broadly endorsed elements of a solution to the challenges posed by childhood cancer in the region, both at the level of individual countries and through supra-national collaboration. Key findings include: the potential role for a pan-regional task force on childhood cancer in advancing collective goals; the import of structured health system guidance to national policy and program development on childhood cancer; and the crucial need for enhanced capacity to monitor and evaluate childhood cancer systems and policies. Conclusion: The fruits of this deliberative process include novel policy-relevant research and advocacy endeavours, and enhanced relationships among diverse regional stakeholders to support evidence and policy development relevant to childhood cancer care in Latin America. Deliberative dialogues hold promise for advancing evidence-informed health system strategies on childhood cancer care in other LMIC contexts.